ARCHAEOLOGICAL EXCAVATIONS AND SCIENTIFIC FINDINGS IN GENGHIS KHAN - Zokir Eshboltaevich Kholikov (Scholar Express Journal, 2021)
The article provides a scientific analysis of the results of archeological excavations on Genghis Khan, one of the most famous monuments of Bactria in antiquity, ie Greece, Bactria and the Kushan Empire, and scientific analogies of material culture
Keywords: Genghis Khan; archeological researches; temple; castle; palace; chronology; scientific analogy; Old Termez; Oykhanum; Greek Bactria; Kushan period